Disentangling Codependency from Empathy: A Steinian Trinitarian Account of the Healing of Personhood - Bliss, Barrie (Lumen et Vita, 2022)
By retrieving Edith Stein’s thought, this paper seeks to propose a spirituality of personhood conducive to healing the psychological root of codependency. In using the broad word codependency, this paper relies upon Charles L. Whitfield’s definition, which understands it as “a disease of lost selfhood.” This paper is working within the intersections of philosophical phenomenology, psychology, and spirituality, and Stein herself is thoroughly immersed in these disciplines. I will begin by delineating what psychologists have labeled codependency as a relational behavior scheme (rather than a diagnosed mental health disorder) and its pervasiveness within those who identify themselves as religious or spiritual using both a clinical and a phenomenological method. Next, by using Edith Stein’s philosophical phenomenological insights regarding the essence of empathy, this paper seeks to disentangle the Gordian knot of empathy and codependency (which I believe to be the core connection between a codependent psyche and those who hold religious and spiritual values). Finally, from Stein’s later works, I will propose a theological trinitarian anthropology that can help heal the lost sense of selfhood that is at the root of codependent ways of relating.